Antifungal Effect: Comparison of Commercial Denture Cleansers and Microwave Energy - Nagham H Kassab; Eman A Mustafa; Radhwan H Hasan (University of Mosul, College of Dentistry, 2009)
and comparing this with microwave sterilization technique on heat cured acrylic resin denture basematerial which was cured by two different techniques. Materials and Methods: thirty two samples ofheat cured acrylic resin denture base material had been used, half of them was cured by conventionalwater bath technique, and the other half by microwave technique. A simple method to measure Candidabiofilm activity using pH change of Stomastat. Modified Sabouraud broth developed and used to evaluatethe efficacy of the following denture cleansers: Chlorhexidine 0.2% and sodium hypochlorite0.5%, and microwave sterilization on Candida albicans biofilm. The initial number of yeasts inoculatedwas correlated with pH value of Stomastat after 24 hours incubation period. Results: The acrylicresin samples that cured by conventional water bath technique were most effectively disinfected bychlorhexidine 0.2%. This demonstrated by increasing the pH value of Stomastat significantly than thecontrol group. The same result was obtained with those samples which were cured by microwave oven.The initial number of Candida albicans cells in Stomastat was significantly decreased than the controlgroup after treatment of acrylic samples with denture cleansers and microwave sterilization technique,while for those samples that cured by microwave technique the least number was obtained after treatmentwith chlorhexidine 0.2%. Conclusion: Both of chlorhexidine 0.2% and sodium hypochlorite0.5% and microwave technique had the ability to disinfect acrylic samples that cured by water bath andmicrowave techniques effectively. However, chlorhexidine 0.2% was the most effective one.